Minor if Entertaining Post-Utopian Nowheres - Prescott, Anne Lake (Renaissance and Reformation / Renaissance et Réforme, 2018)
Not all utopias are truly imaginative, yet minor ones can be instructive or amusing. This article explores the hierarchy-obsessed French Antangil as well as some minor English ones so as to deduce further what so entranced so many about Nowhere’s possibilities. None is as radical as Utopia itself—nor as intelligent. They do, however, show the uses to which a “utopia” can be put. After a glance at Antangil this article moves to a letter from the king of Utopia and thence to Edward Howard’s royalist drama Six Days in a New Utopia (1671), an interesting failure on stage. After a few glances at other utopias the article ends with a grimly amusing avian debate concerning the desire of foreign (French) canaries to settle in Utopia (England), where they will be safe from a persecutory eagle (Louis XIV). Utopia is “nowhere,” but it is a useful nowhere.